Optimization and production kinetics for cellulases by wild and mutant strain of Thermomyces dupontii in stirred tank reactor - Nisar, Kinza; Abullah, Roheena; Kaleem, Afshan; Iqtedar, Mehwish; Iftikar, Tehreema (Acta Scientiarum. Technology, 2022)
The main bottleneck in fermentation technology is scaling up procedure of industrial enzymes according to the biological characteristics of the organism. The current study describes the production kinetics of cellulases in stirred tank reactor by using mutant and wild strains of T. dupontii. The fermentation span of both the strains in bioreactor was examined. It is was found in mutant strain of T. dupontii fermentation time required for optimum production was reduced to 48h as compared to 72h in wild strain. The kinetic studies also exhibited greater value of Âµ (h-1) in case of mutated strain in comparison with wild strain. The effects of some other critical factors like agitation intensity dissolve oxygen, aeration, temperature, size of inoculum and pH was estimated on enzyme production kinetics. The results shows maximum activity of cellulases was attained at 220 rpm, 15% dissolve oxygen, aeration rate 1.5 vvm, 55Â°C, 8 % inoculum size and pH 5.5 for both strains respectively. The higher values of enzyme production kinetics i.e. Yp/x, Qp, Qx and qp in STR in case of mutant strain indicates its superiority over wild strain of T. dupontii. Thus mutant thermophilic T. dupontii might be a potential candidate for industrial applications.